The missing link: Monetary policy and the labor share - Cristiano Cantore; Filippo Ferroni; Miguel A. León-Ledesma (University of Kent, School of Economics, 2018)
The New-Keynesian transmission mechanism of monetary policy has clear implications for the behavior of the labor share. In the basic version of the model, the labor share is negatively related to the price markup and hence is pro-cyclical conditional on monetary policy shocks. However, little empirical evidence is available on the effect of monetary policy on the labor share and its components. We present a comprehensive cross country empirical analysis and find that the data are at odds with the theory. Cyclically, a monetary policy tightening increased the labor share and decreased real wages and labor productivity during the Great Moderation period in the US, the Euro Area, the UK, Australia and Canada. We then examine models allowing for a wide range of nominal and real rigidities that are important to separate the dynamics of the markup and the labor share. We show that models that do a good job at reproducing the responses of real variables to a monetary policy shock are unable to reproduce the responses of the labor share observed in the data.
Keywords: E23; E32; C52; 330; Labor Share; Monetary Policy Shocks; DSGE models